The student voice on integrative teaching and learning of academic literacy at a South African university of technology - Ignatius Khan Ticha; Muhammad Nakhooda; Uloma Nkpurunma Obi (Springer, 2024)
Abstract Academic literacy skills are universally considered as a valuable and integral part of academic development in higher education, yet they often remain peripheral to or are completely absent from many qualifications. At the presently selected institution, there is little consensus on the most effective model to design for and implement as far as academic literacy is concerned, and whether this should be embedded within core curricula, or as a stand-alone, credit-bearing subject. Conspicuously absent in conversations on this matter however, is the student voice, which is what the present study seeks to draw on. An analysis of students' reflections on an integrated model of learning and teaching of academic literacy was evaluated, where the skills are taught within the context of an academic discipline. The academic literacy component was embedded within a single course taught in a Biotechnology qualification. Upon completion of the learning activities, ten students were interviewed, and a questionnaire was administered to a further fifteen students, to gauge feedback on the usefulness of the integrated model of academic literacy. We report that the pedagogy improved and enriched the overall learning experience. Students reflected that the approach enabled better access to Biotechnology content and made the discourse of the discipline more explicit, as they unlocked academic literacy skills, compared to if an academic literacy course was taken alone. More broadly, the study highlights the need to draw on student reflection and experiences in the design and implementation of pedagogies and the value of remaining responsive to student voices.